Comparison of Heart Rate Variability and Heart Rate Recovery Indices in Healthy Young Adults after Submaximal Exercise with and without Music Intervention - Saravanan T; Prashanth K S (RGUHS National Journal of Public Health)
Background Physical exercise places significant demand on the cardiovascular system with heart rate HR increasing during activity and rapidly decreasing post-exercise. The post-exercise reactivation of the parasympathetic nervous system is thought to have a cardioprotective effect. Music is known to modulate emotions and autonomic nervous system activity. This study aimed to assess the effect of music intervention on heart rate variability HRV and heart rate recovery indices HRRI in healthy young adults following a submaximal exercise the 6-minute walk test.Methods The study involved 21 healthy young adults aged 18ndash25 years. Baseline measurements of heart rate HR blood pressure BP respiratory rate RR and heart rate variability HRV were recorded. Participants then performed the 6-minute walk test after which peak HR HRV and HR at 1 and 3 minutes post-exercise were recorded and heart rate recovery index HRRI was calculated. On the intervention day the same procedure was followed. After completing the 6-minute walk test participants listened to a 5-minute veena rendition in Raaga Naata moderate tempo through a mobile phone and headset. During the music session HRV was recorded and HRRI was recalculated and analyzed.Results There were no significant differences seen in the HRV parameters in any of the study conditions. There was a significant increase in HRRI 1 12.571 plusmn 2.694 14.19 plusmn 2.015 P lt 0.001 and HRRI 3 39.476 plusmn 7.38 43.857 plusmn 5.918 P 0.01 with music intervention during recovery as compared to without music.Conclusion Post-exercise music intervention enhanced the rate of heart rate recovery. It can be a useful adjunct to minimize cardiac workload after exercise.